Surface and bulk reactions in borohydrides and amides - Borgschulte, A; Jones, M; Callini, E; Probst, B; Kato, S; Zuettel, A; David, W; Orimo, S (2012)
Complex hydrides such as LiBH4 and LiNH2 exceed the gravimetric hydrogen density of transition metal hydrides by one order of magnitude. However, hydrogen in complex hydrides is covalently bound and arranged in subunits e.g. [NH2]- and [BH4] - with a fixed stoichiometry. Along this line of thought, these compounds can be considered as ordinary ionic compounds. The corresponding pseudo-binary phase diagram comprises a great variety of phases with a high ionic mobility of Li-cations as well as pseudo-anions as measured by diffusion gradients. Using this equilibrium preparation method, we are able to discriminate between stable and meta-stable phases such as Li2BH 4NH2 formed during high-energy ball-milling. We identify Li2BH4NH2 as a mobile intermediate during phase formation. Hydrogen desorption as relevant for their potential use as hydrogen storage does not take place below 200°C as measured by gravimetry. In particular amides, but also borohydrides emit hydrogen, and nitrogen and boron, respectively, containing species (NH3 and BHx, respectively). We probe the bulk and surface exchange of hydrogen in such subunits in LiNH2 and Li2BH4NH2 by hydrogen-deuterium experiments. In contrast to bulk exchange, surface exchange processes occur at very low temperatures - lower than a significant decomposition rate but coincidentally with the appearance of Li2NH comprising high ionic conductivity. The rate limiting step is thus the bulk transport - in agreement with the empirical correlation that the mobility of ions is linked to the hydrogen desorption kinetics of a material (P. A. Anderson et al., Faraday Discuss., 2011, 151, 271-284). However, the bulk transport of ionic species competes with the diffusion of neutral species such as ammonia, being the origin of the unwanted emission of NH3. These results are discussed with respect to the ionic mobility of borohydride and amide materials. © 2012 The Royal Society of Chemistry.